ANALYSIS OF QUANTITATIVE CHARACTERISTICS OF EMISSIONS OF "GREENHOUSE AND THERMAL" GASES DEPENDING ON THE TYPE OF FUEL - Шелешей, Тетяна; Беднарська, Інна; Куца, Аліна; Циганов, Кирило; Олименко, Ірина; Апостол, Ярослав (SWorldJournal, 2023)
The main goal of this article is to conduct a calculated study of the emission level of nitrogen and carbon oxides when burning different fuels at different power plants. Such installations are: boiler units with a circulating fluidized and fixed bed, as